Hubungan Ekspresi Vascular Endothelial Growth Factor (VEGF) dengan Derajat Diferensiasi dan Invasi Limfovaskular pada Karsinoma Urotelial Infiltratif Kandung Kemih - Yenita; Utami, Dini Andri; Agus, Salmiah; Yetti, Husna (Majalah Patologi Indonesia, 2022)
Background Urothelial carcinoma is the most common malignancy in the bladder with an incidence up to 95% and 70-85% of them are bladder infiltrating urothelial carcinoma. To improve the management of bladder urothelial carcinoma, prognostic factors are required. One such factor is angiogenesis, which affects growth, development and metastasis. Vascular endothelial growth factor (VEGF) is the main pro-angiogenic factor to control angiogenesis. Expression of VEGF is correlated with progression of bladder infiltrating urothelial carcinoma, such as grade and lymphovascular invasion. The aim of this study was to determine the correlation of VEGF expression with grade of differentiation and lymphovascular invasion in bladder infiltrating urothelial carcinoma. Methods This research was a retrospective observational cross sectional study with 48 cases of bladder infiltrating urothelial carcinoma in four Anatomical Pathology Laboratory in West Sumatera 2018 and 2019. Samples were reevaluated of HE slide for grade of differentiation and lymphovascular invasion. VEGF expressions in tumor cell s were analyzed using immunohistochemistry staining. Bivariate statistical analysis used Fisher's Exact test and value p<0.05 was considered significant. Results Bladder infiltrating urothelial carcinoma high grade had more positive VEGF expression (91.7%), while low grade had more negative VEGF expression (58.3%). Lymphovascular invasion positive was mostly found with positive VEGF expression (75%). Statistical analysis showed significant correlation between VEGF expression with grade of differentiation (p=0.001) and lymphovascular invasion (p=0.004). Conclusion The conclusion was VEGF expression had significant correlation with grade of differentiation and lymphovascular invasion of bladder infiltrating urothelial carcinoma.